A new light-element multi-principal-elements alloy AlMg2TiZn and its potential for hydrogen storage. (October 2022) - Cermak, Jiri; Kral, Lubomir; Roupcova, Pavla
Abstract: Hydrogen storage in a new-designed multi-principal-elements alloy (MPEA) AlMg2TiZn was studied. The chemical composition of the alloy ranks the alloy into the so-called light-elements family of MPEAs. The alloy was prepared by high energy ball milling and the measurements were carried out using Sieverts method in temperature interval 310°C–370 °C under the hydrogen-gas pressure up to 25 bar. It was found that hydrogen absorption capacity was about 1.35–1.4 wt% H2. Activation energy of hydrogen desorption, Ea = 148 ± 1 kJ/mol H2, was significantly lower than known value for pure Mg. Hydrogen absorption occurred in two steps, A1 and A2. The values of activation energy Ea = 175 ± 12 kJ/mol H2 for rapid absorption A1 and Ea = 195 ± 8 kJ/mol H2 for subsequent slow absorption A2 were close to that for Mg. It was proposed that A1 was related to formation of αMgH2, the second one, A2, was related to formation of βMgH2. Absolute value of hydride formation enthalpies, ΔH = 75 ± 3 kJ/mol H2 and ΔH = 70 ± 2 kJ/mol H2 obtained for A1 and A2, respectively, as well as value of ΔH = 76 ± 1 kJ/mol H2 for desorption were about the same as that for pure MgH2.